WebDASC: a web‐based dietary assessment software for 8–11‐year‐old Danish children. (18th May 2012) - Biltoft‐Jensen, A.; Trolle, E.; Christensen, T.; Islam, N.; Andersen, L. F.; Egenfeldt‐Nielsen, S.; Tetens, I.
Abstract : Abstract: Background: The present study describes the development and formative evaluation of the Web‐based Dietary Assessment Software for Children (WebDASC). WebDASC is part of the OPUS project ('Optimal well‐being, development and health for Danish children through a healthy New Nordic Diet') and was intended to measure dietary change resulting from a school‐based intervention. Methods: WebDASC was developed as a self‐administered tool that could be used by 8–11‐year‐old children with or without parent's aid. The development of WebDASC followed a prototyping approach: focus groups, informal interviews, literature review, and usability tests preceded its release. Special consideration was given to age‐appropriate design issues. Results: In WebDASC an animated armadillo guides respondents through six daily eating occasions and helps them report foods and beverages previously consumed. A database of 1300 food items is available either through category browse or free text search, aided by a spell check application. A type‐in format is available for foods not otherwise found through category browse or text search. Amount consumed is estimated by selecting the closest portion size among four different digital images. WebDASC includes internal checks for frequently forgotten foods, and the following features to create motivation: a food‐meter displaying cumulative weight of foods reported, a most popular food ranking, and a computer game with a high score list. Conclusions: WebDASC was developed as an intuitive, cost‐effective, and engaging method to collect detailed dietary data from 8‐ to 11‐year‐old children. Preliminary testing demonstrated that it was well accepted among children.